1996
DOI: 10.1200/jco.1996.14.4.1156
|View full text |Cite
|
Sign up to set email alerts
|

Minimal toxicity and mortality in high-risk breast cancer patients receiving high-dose cyclophosphamide, thiotepa, and carboplatin plus autologous marrow/stem-cell transplantation and comprehensive supportive care.

Abstract: A comprehensive supportive care approach was associated with a low treatment-related mortality rate of less than 1%. With the observed reduction in treatment-related mortality, it is reasonable to evaluate the efficacy of HDC in women with less than 10 positive nodes and stage II disease in well-designed clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
5
25
1
1
Order By: Relevance
“…These results are significantly better than historical or contemporary data obtained for similar prognosis patients receiving SDC. A number of other phase II trials have also reported encouraging results in high-risk primary disease [61][62][63][64]. ABMTR reported outcomes [43] in high-risk primary disease are consistent with the phase II reports.…”
Section: Hdc For High-risk Primary Breast Cancersupporting
confidence: 81%
“…These results are significantly better than historical or contemporary data obtained for similar prognosis patients receiving SDC. A number of other phase II trials have also reported encouraging results in high-risk primary disease [61][62][63][64]. ABMTR reported outcomes [43] in high-risk primary disease are consistent with the phase II reports.…”
Section: Hdc For High-risk Primary Breast Cancersupporting
confidence: 81%
“…The toxicity appears equivalent to previously published reports in women receiving autotransplants for breast cancer. [11][12][13][14] Although the number of subjects is small, the efficacy of autotransplant in these 13 men with high-risk breast cancer appears similar to results reported in women. 11,12 Outcomes of the patients with metastatic disease were disappointing, however only three patients were available for analysis.…”
Section: Discussionsupporting
confidence: 63%
“…28 Carboplatin has also been used as a part of CTCb and ICE regimens for treatment of various solid tumors with HDC and autologous PBSCT. 3,[28][29][30][31] Calvert et al 47 have documented the importance of dosing by a calculated target formula which compensates for renal function, age and gender when conventional doses of carboplatin are administered. It has been demonstrated that estimated AUC values of carboplatin in several studies overlapped with dosing on a mg/m 2 basis.…”
Section: Upnmentioning
confidence: 99%
“…3 Carboplatin as a part of ICE (ifosfamide, carboplatin and etoposide) and CTCb (cyclophosphamide, thiotepa, carboplatin) HDC regimens has been used for the treatment of various solid tumors with autologous PBSCT. 3,[27][28][29][30][31] Based on these observations, we hypothesized that a HDC regimen of thiotepa, melphalan and carboplatin would have substantial antitumor activity. We report the results of a dose escalation study of carboplatin administered with a fixed dose of 500 mg/m 2 thiotepa and 100 mg/m 2 melphalan to determine the maximum tolerated dose (MTD) in patients with refractory malignancies.…”
mentioning
confidence: 99%